LEGAL CHARACTERISTICS OF CAUSES FOR THE PAYMENT OF ONE-TIME CASH ASSISTANCE TO MILITARY SERVANTS - Пивовар, Ірина Вікторівна; Пивовар, Юрій Ігорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: implementation of legal analysis and delineation of the factual causes for the payment of one-time financial assistance to military personnel, as well as setting restrictions for the application of such grounds. Research methods: formal legal, which contributed to the analysis of legislative regulations, individual acts; methods of comparison, classification and generalization, which made it possible to single out the types of states of human life (military personnel) as the basis for the appointment of a benefit; modeling method - contributed to the formulation of a conclusion that could be used in the law enforcement practice of authorized authorities. Results: an algorithm is proposed for analyzing the normative grounds for the payment of one-time monetary assistance to servicemen in connection with the establishment of disability or disablement incapacity. Discussion: discussion for the implementation (appointment) of the payment of one-time monetary assistance for military personnel should identify and distinguish between the following two states of a person: a state of disability; disability condition. These states are the actual basis for the appointment of the indicated financial assistance; the specified states by the nature of occurrence, social status, subject of appointment, sphere of life, the factual grounds (causes) of the establishment, social consequences differ, do not coincide in volume and content, and in degree constitute different group series. The authors substantiate the conclusion that in cases of resolving the issue of applying the provisions of paragraph 1 of paragraph 4 of Article 16-3 of the Law of Ukraine «On social and legal protection of military personnel and members of their families» to receive additional payments of the difference between the amount of previously received one-time cash assistance and a new one-time financial assistance for a period of up to two years, it is considered appropriate to recognize the state of disability and the state of partial loss of working capacity as independent states, without the possibility of their combination.